PHARMACOLOGICAL IMPACT OF HOSPITALIZATION IN AN ACUTE GERIATRIC UNIT - Martinez-Velilla, N. (Innov Aging, 2017)
The impact of hospitalization on the treatment of elderly patients has not been widely studied. Previous studies examine some treatment characteristics in an isolated way and also provide mixed results and few until now have explored the modification of treatments during hospitalization with a mixed comprehensive approach. We have conducted a retrospective observational study in 235 admitted patients, and compared polypharmacy (≥5 and ≥10 drugs), potentially inappropriate prescribing or potentially omitted prescription (PIP-POP), drug interactions, the use of drugs with impaired renal function and the anticholinergic load of the treatments before and after admission to hospital. Their relationship with mortality, readmissions and emergency visits after a six-month follow-up were also analyzed by multivariate logistic regression. We found that the total number of drugs increases (9.1 vs. 10.1 p<0.001), without increasing chronic drugs (8.5 vs. 8.3). There were no significant variations in the number of patients with polypharmacy (86.5% vs. 82.2%), those who presented inappropriate prescribing criteria (68.5% vs. 71.5% STOPP; 58% vs. 58% START) or those presenting interactions (82.5% vs. 83.5%). Those receiving drugs with anticholinergic effect tend to increase but without reaching statistical significance (39.5% vs. 44.5%; p=0.064). An association was found between hyperpolypharmacy and the risk of readmission (OR 2.302; 95% CI 1.197–4.425), and emergency visits (OR 1.928; 95% CI 1.049–3.546).